BREAST CANCER PATIENTS’ COMPLIANCE ON CHEMOTHERAPY: A DESCRIPTIVE STUDY - Vici Triyunita Sabiyanto; Restuning Widiasih; Tetti Solehati (Journal of Maternity Care and Reproductive Health, 2019)
Breast cancer is the most women cancer in the world, including Indonesia. Some patients stop breast cancer treatment which is impacted to patients' conditions. In chronic diseases, therapy compliance is important for reach successful therapy however study that assess breast cancer patients’ compliance on chemotherapy is limited. The purpose of this study was to describe patient factors that can affect therapy compliance. This research used descriptive quantitative method and respondents were chosen using the accidental sampling technique. The data were gathered at one of the halfway houses in Bandung. Data were collected using a questionnaire. Data were analyzed by univariate analysis and described by frequency distribution. The results showed that 26 respondents (84%) were obedient to chemotherapy. There were 28 respondents (90.3%) because they did not carry out alternative medicine and 26 respondents (83.9%) had because they put aside work and related affairs to do chemotherapy. In conclusion, the majority of respondents were obedient to chemotherapy. There are patient factors that can improve chemotherapy compliance, there are chosen therapy factor and demographic and economic factors. Development of another halfway houses could be carried out, because of the result of this research, representing many breast cancer patients feels easier to obedient the sequence of therapy.Keywords: Breast cancer, therapy compliance, halfway house.